2014
DOI: 10.1073/pnas.1320873111
|View full text |Cite
|
Sign up to set email alerts
|

Brf1 posttranscriptionally regulates pluripotency and differentiation responses downstream of Erk MAP kinase

Abstract: AU-rich element mRNA-binding proteins (AUBPs) are key regulators of development, but how they are controlled and what functional roles they play depends on cellular context. Here, we show that Brf1 (zfp36l1), an AUBP from the Zfp36 protein family, operates downstream of FGF/Erk MAP kinase signaling to regulate pluripotency and cell fate decision making in mouse embryonic stem cells (mESCs). FGF/Erk MAP kinase signaling up-regulates Brf1, which disrupts the expression of core pluripotency-associated genes and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…RBPs are important regulators of mRNA stability through binding to the 3 0 untranslated regions of mRNAs (46). ZFP36L1 is an RBP that has been reported to regulate mouse embryonic stem cell fate through binding to mRNAs encoding pluripotency factors including Nanog (47). Here, we found that ZFP36L1 is phosphorylated and inactivated by the p38 substrate MK2, leading to stabilization of Nanog and Klf4 mRNA in TNBC cells.…”
Section: Discussionmentioning
confidence: 69%
“…RBPs are important regulators of mRNA stability through binding to the 3 0 untranslated regions of mRNAs (46). ZFP36L1 is an RBP that has been reported to regulate mouse embryonic stem cell fate through binding to mRNAs encoding pluripotency factors including Nanog (47). Here, we found that ZFP36L1 is phosphorylated and inactivated by the p38 substrate MK2, leading to stabilization of Nanog and Klf4 mRNA in TNBC cells.…”
Section: Discussionmentioning
confidence: 69%
“…Through the activation of Mek and Erk, Fgf4 leads to the downregulation of Nanog at the transcriptional level, but also destabilizes Klf2 and Klf4 protein through Erk-dependent phosphorylation [22,23]. Moreover, Gsk3, which can mediate Wnt signalling has a differentiation promoting effect by repressing several pluripotency factors, [14], c [15], d [16], e [17], f [18], g [19], h [20], i [21], j [22], k [23], l [24], m [25], n [26], o [27].…”
Section: Sex Differences In Murine Embryonic Stem Cellsmentioning
confidence: 99%
“…Klf4 in turn induces the E3 ubiquitin ligase March5, which promotes the pluripotent state by inhibiting the Mek/Erk cascade [14]. Moreover, the AU-rich element mRNA binding protein Brf1 has been identified as an Erk target gene in mESCs and has been shown to bind and destabilize the mRNAs of several pluripotencyassociated genes, including Nanog [21]. This mechanism might mediate the long known Erk-dependent downregulation of Nanog [42].…”
Section: The Pluripotency-associated Signalling Networkmentioning
confidence: 99%
“…AUBPs are known to be developmentally important regulators of splicing, stability, translation, and localization, and Brf1 is critical in embryogenesis: knockout mice die by E10.5 (Stumpo et al, 2004). A recent study found that activation of the FGF-Erk signaling pathway, which stimulates mouse ESC differentiation, leads to upregulation of Brf1 (Tan and Elowitz, 2014). Brf1 overexpression under pluripotency conditions impaired ESC proliferation, and under differentiation conditions it promoted the acquisition of mesendoderm fate.…”
Section: Regulation Of Mrna Stabilitymentioning
confidence: 99%